Preliminary investigation of the circadian rhythms of wild-collected Neurospora strains. - L W Morgan; JERRY F FELDMAN (Fungal Genetics Reports, 1998)
A medium that allows for measurement of circadian rhythms in wild-collected strains of Neurospora is reported. Preliminary results with N. intermedia strains from four different latitudes suggest natural variation in clock-affecting loci.